The Eternal Present: A Contribution on Constancy and Change II. The Beginnings of Architecture - Giedion, S. (1964)
The A. W. Mellon Lectures in the Fine Arts, 1957. The National Gallery of Art, Washington, D.C.; Bollingen Foundation. Distributed by Pantheon Books (Random House, Inc.); spez. parts I: The differing destinies of Egypt and Sumer; II. The eggshells of prehistory; III. Creating an anthropomorphic cosmos; IV. Constancy and change in the mode of expression; V. The origins of monumental architecture: Mesopotamia; VI. Ziggurats: Stairways of the gods.